Establishment of heat stress index to improve thermal comfort among industrial operators in Malaysia - Mohd Suadi Nata, Dayana Hazwani (2017)
Malaysia is a tropical climate country with hot and humid condition throughout the year. The hot working environment in the industrial increases the challenges of body homeostasis to induce heat stress and interferes with thermal comfort. For this problem, there is no specific standard or guideline of heat adaptation for the industrial operators in Malaysia to overcome the problems. In addition, no studies have been carried out in Malaysia to model the exposure of heat to workers with thermal comfort. Therefore, the aim of this study is to establish the prediction index of heat stress index in order to improve the thermal comfort among industrial operators in Malaysia. Two phases were conducted, namely (1) Phase 1: Cross-sectional study, and (2) Phase 2: Experimental study. The cross-sectional study was conducted in palm oil mill, steel industry and manufacturing plant in Malaysia to collect the 464 of male industrial workers who were identified exposed to the heat during working. Data collection consisted of the walk-through assessment, questionnaire, environmental monitoring, and personal assessment. The study showed that the mean of WBGTin =30.69±0.99°C, exceeding the ACGIH TLVs which suggested to be 28.2°C for work and rest regime (75% work and 25% rest). In this study, therefore, 100% of operators were identified to suffer heat stress during working y. The perception of comfort checklist showed that 82.1% of operators felt discomfort while working in their workplace. In addition, the variables involved in this study were acute heat symptoms score which recorded as the highest Beta value (B = 0.480, p <0.001), followed by, WBGTin (B = 0.150, p<0.001), metabolic workload (B= 0.1, p=0.11), body core temperature (B=0.087, p =0.015), drinking volumes (B=-0,163, p<0.001) and relative humidity (B = -0.190, p <0.001). An experimental work was conducted between 60 operators in phase 2 for comparison and validation of the predictive index with the existing procedure to determine thermal comfort value, humidex and perception of thermal comfort checklist. The result showed there was a significant positive correlation between the predictive index and humidex, r = 0.754, p = 0.01, and there was no significant correlation with the perception of thermal comfort checklist (r= 0.032). In addition, the receiver operating characteristic (ROC) curve showed that rule performed more accurately in predictive index (area under the curve = 0.893) compared to perception of thermal comfort checklist (area under the curve = 0.524). All physiological variables exhibited significant difference with predictive index, namely body core temperature (p<0.001), heart rate (p =0.001), systolic blood pressure (p<0.001) and diastolic blood pressure (p= 0.07). The discriminate function revealed a significant association between groups (comfort and discomfort) with all physiological variables, accounting for 62.41% of between group variability. Moreover, the establishment of heat stress index was integrated into visual basic application (VBA) in Microsoft Excel. The index was found to be able to express comprehensive index which included the individual perception factors, environmental and physiological changes for indoor industries. This index was proved to be more user-friendly and applicable in which the variability of determination of thermal comfort was better than other indexes. In conclusion, the establishment of heat stress index in this study indicated the ability of this index to represent the indoor heat stress condition, as well as applicable and a simple measurement which consisted of all the associated factors (individual, environmental and physiological variables) in heat stress and thermal comfort.